From equity to renewal: multi-factor evaluation of urban park accessibility in community life circles, Taijiang District, Fuzhou - Wang, Yuhan; Yang, Jianfeng; Hong, Yining; Ma, Guoli; Fu, Yeting; Lin, Yan; Lan, Siren; Li, Fangying (Frontiers in Environmental Science, 2025)
Urban development in China has entered a stage of stock-based renewal, with greater emphasis on optimizing existing resources. As a public resource, urban parks play a crucial role in promoting public health through equitable distribution. Traditional, extensive, top-down allocation models can no longer meet residents’ needs, and the diverse demands of various social groups for parks are often overlooked. In response, the concept of community life circles has emerged as a more human-centered and efficient planning strategy. This study, focusing on spatial and social equity, approaches the issue through the perspective of community life circles. By incorporating park quality, group demand heterogeneity, and API-based path planning, it refines the dynamic age-grouped Gaussian-based two-step floating catchment area (D-AG2SFCA) method to assess park accessibility and supply–demand relationships under three community life circle scenarios (5-, 10-, and 15-min walking distances). From the perspective of group-differentiated equity, this study further identifies disadvantaged areas in park access under the three scenarios, as well as the degree of spatial differentiation in resource availability for disadvantaged groups. Finally, by integrating accessibility, supply–demand relationships, and location quotients, this study constructs a multi-factor evaluation system to determine priorities for urban park renewal and proposes targeted optimization strategies.